Expression of chitinase A (chiA) gene from a local isolate of Serratia marcescens in Coleoptera-specific Bacillus thuringiensis - Okay, S.; Tefon, B. E.; Özkan, Melek; Ozcengiz, G. (Oxford Univ Press, 2008)
Aims: The present study focused on cloning and expression of chiA gene from a highly chitinolytic local isolate of Serratia marcescens in an anti-Coleopteran Bacillus thuringiensis and comparison of the characteristics of the native and recombinant ChiAs. Methods and Results: chiA gene from Ser. marcescens was cloned, sequenced and compared with the previously cloned chiA genes. chiA gene was PCR cloned and expressed in anti-Coleopteran B. thuringiensis strain 3023 as verified by Western blot analysis. Specific ChiA activity of the recombinant B. thuringiensis (strain 3023-SCHI) reached its highest level at 21st hour of growth (16.93 U mg(-1)), which was 5.2- and 1.3-fold higher than that of its parental strain and Ser. marcescens, respectively. Temperature and pH effects on native and recombinant ChiAs were next determined. The recombinant plasmid was quite stable over 240 generations. Conclusions: Serratia marcescens ChiA was heterologously expressed in an anti-Coleopteran B. thuringiensis at levels even higher than that produced by the source organism. Significance and Impact of the Study: Bacillus thuringiensis 3023-SCHI co-expressing anti-Coleopteran Cry3Aa protein and Ser. marcescens chitinase offers a viable alternative to the use of chitinolytic microbes/enzymes in combination with entamopathogenic bacteria for an increased potency because of synergistic interaction between them.
Keywords: Bacillus thuringiensis; biocontrol; bioinsecticides; chitinases; Cry3Aa protein; Serratia marcescens